Economic Analysis and Compressive Strength of Concrete, Cost and Utilization Time of Carbon-Sulfur and Dirty Sulfur Solid Waste - Vian Marantha Haryanto; Agus Suroso; Mawardi Amin; Sherafina Reni Cahayanti (Syntax Idea)
This study aims to analyze whether carbon-sulfur and dirty sulfur solid waste added materials can be used for concrete manufacturing, obtain and analyze the formulation of a 2% carbon sulfur mixture with concrete compressive strength, and the cost value. This research is experimental where this study aims to determine the relationship between concrete compressive strength and compression testing machine tools. The test specimen made in this experiment is a concrete cylinder. The data form of this study is numeric. The conclusions that can be drawn from the discussion for carbon-sulfur and dirty sulfur solid waste research are as follows: Carbon sulfur &; dirty sulfur from the results of the laboratory test determination shows that the toxicity characteristics leaching procedure (TCLP) value and total concentration (TK) have not exceeded the Category B threshold according to PP22 of 2021.